Exploring 5,7-dimethoxyflavone from Piper ornatum as a novel anti-breast cancer candidate: insights from in silico analysis - A. U. Rohmatika; T. Demircan; A. K. M. Jamil; F. R. P. Dewi (Brazilian Journal of Biology)
Abstract This study investigates the potential of the compound 5,7-dimethoxyflavone (5,7-DMF) found in Piper ornatum as an anti-breast cancer agent using an in silico approach. The study targeted three major mechanisms involved in breast cancer progression: the ability of 5,7-DMF to inhibit kinase activity, act as a competitive inhibitor of cyclooxygenase 2 (COX-2) and nitric oxide synthase 2 (NOS2). This was investigated through molecular simulation by assessing drug-likeness, toxicity, membrane permeability, bioactivity, specific docking with AutoDock Vina integrated with PyRx 8.0, as well as molecular dynamics simulation using CABS-flex 2.0. Molecular docking results showed that 5,7-DMF has a high binding affinity towards the COX-2 target and inhibits kinase activity. This study also revealed significant interactions between 5,7-DMF and the COX-2 active site, supporting its potential as an anti-breast cancer agent. These results provide a solid basis for the further development of 5,7-DMF as a potential drug candidate against breast cancer.